POTENTIALS OF SOCIO-ECONOMIC TREE SPECIES IN DUTSE LOCAL GOVERNMENT AREA OF JIGAWA STATE, NIGERIA - Lawal, A. A.; Salami, K. D.; Amina, H. G.; Oladipupo, A. Y.; Dagauda, A. M. (FUDMA JOURNAL OF SCIENCES, 2023)
Population growth affects forest ecosystem due to the diverse benefits it provides. The rate of disappearance of indigenous trees species in Dutse has remained a threat to conservation and ecosystem managers. This study examines the local utilization of economic trees and factors affecting their availability. Multistage sampling technique was used. 120 sets of questionnaires were administered while the data were subjected to descriptive statistical analysis. Eighteen tree species were discovered to be most economical. (25%) Prosopis africana had the highest percentage frequency, followed by (16.7%) Parkia biglobosa and (12.5%) Sclerocarya birrea respectively. 38.3% of the respondents utilized the trees for food, 25% used it as herbal therapy, 17.5% used it as fuel wood while 7.5% used it for furniture. A good number of tree species are used for food and medicinal remedies more than any other use from. However, some other native tree species of socio-economic importance have disappeared. This implies that, if the rate of loss of these economic trees in the study area is not checked, the economic welfare of the most populated rural communities may be affected. In conclusion, attention should be given to conservation through teachings in relevant aspects such as forestry, rural development, agro-forestry and environmental science which will provide a foundation for sustainability in the study area. Enrichment planting should be carried out to support the socio-economic welfare of the people and help re-introduce some disappearing native species.
Keywords: socio-economic, indigenous trees, fodder, fuel wood, frequency